Pengaturan Bantuan Pangan Non Tunai di Kota Malang (Studi Peraturan Walikota Nomor 6 Tahun 2020 Tentang Petunjuk Teknis Bantuan Pangan Non Tunai Daerah) - Haru Permadi; Oppy Pramudya Wisnu Wardhana (UNES Law Review, 2023)
The Non-Cash Food Assistance Program is a government initiative that aims to provide monthly food assistance to eligible families, followed by Sub-District Social Welfare Workers. The program has been implemented in 514 districts and cities in Indonesia, including one special city. The location in question is Malang City. The research methodology used in this study is descriptive qualitative. The descriptive qualitative approach is used as a means to investigate and analyze observations and findings within a particular domain or discipline. The research findings show that the Non-Cash Food Assistance Program has provided assistance to a total of 7,226 beneficiary families, as reported by the Ministry of Social Affairs. Malang City consists of 57 urban villages spread across 5 sub-districts. The outcome measures from this study have proven to be very important in helping beneficiaries effectively reduce daily expenditures, thus allowing the organization to generate higher profits that can be utilized to meet additional needs. Indirectly, this can be interpreted as an indication of their improved social welfare. Therefore, it can be said that this program has had a significant impact on poverty reduction efforts in the Malang urban area.